Viewing African and Asian elephants at accredited zoological institutions: Conservation intent and perceptions of animal welfare. Issue 6 (26th September 2018) - Miller, Lance J.; Luebke, Jerry F.; Matiasek, Jennifer
Abstract : African and Asian elephants are popular within zoos, however there is currently limited information on how viewing them impacts zoo visitors. The goal of the current study was to examine the relationship between viewing elephants in zoos accredited by the Association of Zoos and Aquariums and zoo visitors' reported conservation intent and perceptions of animal welfare. Visitors were systematically selected to fill out questionnaires following elephant observation at nine facilities throughout North America. Questions included information on conservation predispositions, exhibit experience, exhibit perceptions, animal welfare perceptions, emotional experience, learning outcomes, conservation intent, and demographics. Results suggest that observing elephants engaged in a variety of species‐typical behaviors and having an up‐close experience was significantly correlated to visitors having a positive emotional response. The positive emotional response, combined with visitor conservation predisposition had a significant positive relationship with reported interest in getting involved in conservation. Perceptions of animal welfare were significantly related to a positive emotional experience driven by seeing animals engaged in a variety of active species‐typical behaviors as well as exhibit perceptions and whether or not visitors thought it was important to have elephants in zoos. Exhibit perception was primarily correlated with exhibit size. The results provide factors that could help to increase visitor interest in conservation as well as the potential impact of viewing elephants in an accredited zoo. Facilities can use this information to help ensure their visitors have similar type experiences in order to inspire visitors' interest in conservation as well as positive perceptions of animal welfare.